Stunting and severe stunting among children under-5 years in Nigeria: A multilevel analysis. Issue 1 (December 2017) - Akombi, Blessing; Agho, Kingsley; Hall, John; Merom, Dafna; Astell-Burt, Thomas; Renzaho, Andre
Abstract Background Stunting has been identified as one of the major proximal risk factors for poor physical and mental development of children under-5 years. Stunting predominantly occurs in the first 1000 days of life (0–23 months) and continues to the age of five. This study examines factors associated with stunting and severe stunting among children under-5 years in Nigeria. Methods The sample included 24, 529 children aged 0–59 months from the 2013 Nigeria Demographic and Health Survey (NDHS). Height-for-age z-scores (HFAz), generated using the 2006 World Health Organisation (WHO) growth reference, were used to define stunting (HFAz < −2SD) and severe stunting (HFAz < −3SD). Multilevel logistic regression analyses that adjusted for cluster and survey weights were used to determine potential risk factors associated with stunting and severe stunting among children under-5 years in Nigeria. Results The prevalence of stunting and severe stunting were 29% [95% Confidence interval (Cl): 27.4, 30.8] and 16.4% [95%Cl: 15.1, 17.8], respectively for children aged 0–23 months, and 36.7% [95%Cl: 35.1, 38.3] and 21% [95%Cl: 19.7, 22.4], respectively for children aged 0–59 months. Multivariate analysis revealed that the most consistent significant risk factors for stunting and severe stunting among children aged 0–23 months and 0–59 months are: sex of child (male), mother's perceived birth size (small and average), household wealth index (poor and poorest households), duration of breastfeeding (more than 12 months), geopolitical zone (North East, North West, North Central) and children who were reported to having had diarrhoea in the 2 weeks prior to the survey [Adjusted odds ratio (AOR) for stunted children 0–23 months = 1.22 (95%Cl: 0.99, 1.49)];[AOR for stunted children 0–59 months = 1.31 (95%Cl: 1.16, 1.49)], [AOR for severely stunted children 0–23 months = 1.31 (95%Cl: 1.03, 1.67)]; [AOR for severely stunted children 0–59 months = 1.58 (95%Cl: 1.38, 1.82)]. Conclusions In order to meet the post-2015 sustainable development goals, policy interventions to reduce stunting in Nigeria should focus on poverty alleviation as well as improving women's nutrition, child feeding practices and household sanitation.